2012
DOI: 10.3130/jaabe.11.407
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Energy Consumption by AC due to Air Tightness and Ventilation Strategy in Residences in Hot and Humid Climates

Abstract: This paper proposes strategies for reducing energy consumption for cooling in residences in hot and humid climates. Based on the results of fieldwork measurements and questionnaire surveys, a simulation of indoor thermal environments in consideration of air conditioner operation was carried out, in order to evaluate energy consumption by air conditioners. This simulation program takes into account both heat and moisture transfer in building materials. In order to simplify the calculation and due to lack of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Recently occupants are likely to use air conditioners in achieving comfortable indoor environment in tropical climate. The reliant on mechanical systems for health and comfort level has increasing the energy consumption in residential building [17]. The buildings sector consumed the large amount of energy during the utilization phase of the building for heating and cooling purposes [18].…”
Section: Indoor Thermal Environment In Residential Buildingmentioning
confidence: 99%
“…Recently occupants are likely to use air conditioners in achieving comfortable indoor environment in tropical climate. The reliant on mechanical systems for health and comfort level has increasing the energy consumption in residential building [17]. The buildings sector consumed the large amount of energy during the utilization phase of the building for heating and cooling purposes [18].…”
Section: Indoor Thermal Environment In Residential Buildingmentioning
confidence: 99%
“…32 Uno et al. 33 investigated the air-tightness and ventilation strategy of tropical houses in Surabaya city in Indonesia. The study based on simulated and measured data revealed that high air-tightness of air-conditioned room in combination with night natural ventilation of non-air-conditioned rooms have produced the best energy saving result.…”
Section: Building Designs and The Role Of Subdivisionsmentioning
confidence: 99%
“…It is proved that the combination can lower the average operative temperature to 28.5°C (Susumu, Satoshi, and Tetsu 2015). Besides, Uno and Hokoi researched on the reduction of energy consumption by AC due to ventilation strategy as well as building airtightness of residences in hot and humid climates by computational fluid dynamics (CFD), pointing out the influence of airtightness and ventilation pattern on reducing energy consumption (Uno et al 2012).…”
Section: Introductionmentioning
confidence: 99%